Covid-19 and Mental Health Deterioration among BAME Groups in the UK - Eugenio Proto; Climent Quintana-Domeque (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We use the UK Household Longitudinal Study and compare pre- (2017-2019) and post-Covid-19 data (April 2020) for the same group of individuals to assess and quantify changes in mental health among ethnic groups in the UK. We confirm the previously documented average deterioration in mental health for the whole sample of individuals interviewed pre- and post-Covid-19, and uncover four new facts. First, ethnicity predicts mental health deterioration when interacted with gender. Among men, BAME individuals experience a higher deterioration in mental health compared to British White individuals. However, among women, the deterioration in mental health is similar for both BAME and British White individuals. Second, the gender gap in mental health deterioration is only present among British White individuals and not among BAME individuals. Third, the drop in mental health among women and BAME men is very similar. Finally, there is substantial heterogeneity across BAME groups. The BAME group of Bangladeshi, Indian and Pakistani appears to be driving the difference in the gender gap in mental health deterioration between British White and BAME individuals. We call for additional research on the effects of the Covid-19 pandemic across different ethnic groups, and urge both policy makers and researchers to allocate resources to collect larger sample sizes of minority ethnic groups.
Keywords: I10; J10; J15; 330; GHQ-12; wellbeing; mental health; mental distress; ethnicity; gender